For Me and My Gal - Berkeley, Busby; Daniels, William; Garland, Judy; Kelly, Gene; Eggerth, Marta (Warner Archive Collection, 2022)
After a late-night cup of coffee, vaudevillians Jo Hayden and Harry Palmer sit at a piano and work a song. Moments later, Jo realizes she's found exactly what she wasn't looking for: a partner. And with Judy Garland as Jo and Gene Kelly as Harry, the partnership isn't just ideal. It's a film fan's dream come true. Kelly debuts and Garland dazzles in this Busby Berkeley-directed tale of a song-and-dance pair who take on tank towns, tough times and World War I while struggling for show-biz success. A hit parade of era tunes paces the film, including the wowser "Ballin' the Jack" and the sweetly harmonized title tune. Bursting with vitality and old-fashioned charm, "For Me and My Gal" is for the ages. [Cover]